Design, Fabrication, and Testing of a Bulk Micromachined Inertial Measurement Unit - Honglong Chang; Qiang Shen; Zhiguang Zhou; Jianbing Xie; Qinghua Jiang; Weizheng Yuan (Sensors, 2010)
A bulk micromachined inertial measurement unit (MIMU) is presented in this paper. Three single-axis accelerometers and three single-axis gyroscopes were simultaneously fabricated on a silicon wafer using a bulk micromachining process; the wafer is smaller than one square centimeter. In particular, a global area optimization method based on the relationship between the sensitivity and layout area was proposed to determine the layout configuration of the six sensors. The scale factors of the X/Y-axis accelerometer and Z-axis accelerometer are about 213.3 mV/g and 226.9 mV/g, respectively. The scale factors of the X/Y-axis gyroscope and Z-axis gyroscope are about 2.2 mV/o/s and 10.8 mV/o/s, respectively. The bias stability of the X/Y-axis gyroscope and the Z-axis gyroscope are about 2135 deg/h and 80 deg/h, respectively. Finally, the resolutions of X/Y-axis accelerometers, Z-axis accelerometers, X/Y-axis gyroscopes, and Z-axis gyroscopes are 0.0012 g/ √Hz, 0.0011 g/ √Hz, 0.314 °/s/ √Hz, and 0.008 °/s/ √Hz, respectively.